2020
DOI: 10.1186/s12951-020-00618-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the cagW-based gene vaccine on the immunologic properties of BALB/c mouse: an efficient candidate for Helicobacter pylori DNA vaccine

Abstract: Background: Helicobacter pylori (H. pylori) infect more than half of the world population, and they cause different serious diseases such as gastric carcinomas. This study aims to design a vaccine on the basis of cagW against H. pylori infection. After pcDNA3.1 (+)-cagW-CS-NPs complex is produced, it will be administered into the muscles of healthy BALB/c mice in order to study the effect of this DNA vaccine on the interleukin status of mice, representing its effect on the immune system. After that, the result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Polymers are also used as delivery vehicles for mRNA, DNA, and/or adjuvants in vaccines in various forms and morphologies because of their excellent stability. 102 For example, Chehelgerdi et al prepared a cagW‑based DNA vaccine loaded with chitosan nanoparticles; 103 upon injecting mice with this vaccine, the expression of cagW increased on the 7th day and then gradually decreased, reaching a minimum on the 45th day. Furthermore, they found that vaccination significantly increases cellular immunity.…”
Section: Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers are also used as delivery vehicles for mRNA, DNA, and/or adjuvants in vaccines in various forms and morphologies because of their excellent stability. 102 For example, Chehelgerdi et al prepared a cagW‑based DNA vaccine loaded with chitosan nanoparticles; 103 upon injecting mice with this vaccine, the expression of cagW increased on the 7th day and then gradually decreased, reaching a minimum on the 45th day. Furthermore, they found that vaccination significantly increases cellular immunity.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…This suggested that the vaccine exhibited a protective effect against H. pylori in mice. 103 In addition to chitosan, polymers such as HP55 (a special type of hydroxypropyl methylcellulose phthalate)/D and poly(lactic-co-glycolic acid) (PLGA) have also been used as delivery systems for vaccines. 104 For example, Tan et al designed an oral dual-antigen epitope and dual-adjuvant vaccine based on the urease of H. pylori and cholera toxin B subunits and delivered it with HP55/PLGA nanoparticles.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…In the first approach based on type IV secretion system antigens, Chehelgerdi and Doosti [122] used CagW protein as a probable functional analog of the structural VirB6 protein from the type IV secretion system. In the plasmid-based DNA vaccine strategy, the gene coding CagW protein was delivered in pcDNA-3.1 at 100 µg/mouse of plasmid encapsulated or not in chitosan nanoparticles into mice intramuscularly 5 times within 45 days.…”
Section: Vaccinesmentioning
confidence: 99%
“…Helicobacter pylori ( H. pylori ) is a bacteria that may cause a variety of illnesses, including mucosal lymph tissue, peptic ulcers, and stomach cancer (Chehelgerdi & Doosti, 2020 ; Lai et al, 2023 ). H. pylori is mostly connected with stomach infections, but it has also been linked to other illnesses (Kargar et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%